Antonio Gómez-Moriana, La subversion du discours rituel. Éditions du Préambule, Longueuil-Québec, 1985; 167 pp. - Bubnova, Tatiana (El Colegio de México, 1987)
Se reseñó el libro: La subversión du discours rituel